On being a PhD student of Robert Harper. (13th January 2022) - DREYER, DEREK; PIERCE, BENJAMIN C.
Abstract: The Robert Harper Festschrift includes articles by three of Bob's students and colleagues—Karl Crary, Andrzej Filinski, and Jonathan Sterling. Each of these articles touches on themes that are central to Bob's research: module system design, proof-directed program development, and (to use Bob's term) "computational trinitarianism". In this foreword to the Festschrift, we have additionally compiled reminiscences of Bob Harper from his PhD students. We invited them to reflect on their experiences working with and learning from Bob. We believe these reminiscences, presented in chronological order of dissertation date, deliver a most fitting tribute to Bob in honor of his 64th birthday.